Efeitos do acetato de deslorelina sobre a produção in vivo e in vitro de embriões de gatas domésticas - Ackermann, Camila Louise [UNESP] (2015)
Deslorelin acetate promotes a long, safe and efficient contraception; however reversibility is consider progressive and asynchronous. We aim to evaluate the effects of deslorelin acetate on in vitro and in vivo embryo production in domestic cats. For that 2 experiments were performed. Experiment 1: The objective was to investigate the effect of contraceptive treatment with deslorelin acetate in in vitro embryo production and oocyte recovery in domestic queens. Twenty one queens (Treated n=11 and Control n=10) and one tom were used. Eleven queens were treated with deslorelin acetate (4.7mg/animal) during 6 months. Thereafter all females (treated and control) were spayed and the ovaries were included in in vitro embryo production routines (PIV). Rate of COC recovery was submitted to t test. Cleavage and blastocyst rate were expressed in percentage and submitted to Fisher's exact test. All analyses were performed in GraphPad Pisma v5.0 program, P < 0.05. One female developed galactorrhoea and was removed from experimental group. In Control group we recovered 18.4±3.21 of COC I, cleavage rate was 55.97% and blastocyst rate was 33.99%.In Treated group we recovered 8.3±1.15 of COC I, cleavage rate was 60.24% and blastocyst rate was 36%. Statistical difference was only observed in COC recovery, were treated cats had fewer than control group. Although we didn't found differences on embryo production, individual variation must be considered. Experiment 2: We aimed to evaluate in vivo embryo production, trough pregnancies, and also identify estrogen (ER-α) and progesterone (PgR) receptors in uterus and FSH (FSH-R) and LH (LH-R) receptors in ovaries from queen treated with deslorelin acetate. We used 25 queens and one tom, 15 queens were treated with deslorelin acetate (4.7mg/animal) for 3 months. After that, all implants were removed and estrous and ovulation was induced. After 24hs five queens were maintained with one tom and mating was ...